Territory and imagined places - Silva, Armando (Benemérita Universidad Autónoma de Puebla, 2019)
The real world is increasingly imagined and less physical, and this affects the concept we have of territory: how it develops in the new social and technological territorialities is the question proposed by this argument. The ways of propagating the imaginary from contagion and social contact are examined, and it is found that these same strategies correspond to the ways, in which networks operate, to establish, then, a comparison between the cognitive of the imaginary and the digital of the Format. The inclusion of art as a contemporary paradigm serves as support for the final notes where it is argued that the world becomes increasingly mental and this generates other territorialities that announce remains of the present-future.